Targeting macrophage Histone deacetylase 3 stabilizes atherosclerotic lesions. Issue 9 (9th July 2014) - Hoeksema, Marten A; Gijbels, Marion JJ; Van den Bossche, Jan; van der Velden, Saskia; Sijm, Ayestha; Neele, Annette E; Seijkens, Tom; Stöger, J Lauran; Meiler, Svenja; Boshuizen, Marieke CS; Dallinga‐Thie, Geesje M; Levels, Johannes HM; et al.
<x xml:space="preserve">Abstract</x> Hdac3 is shown to be an important modulator of the fibrotic phenotype of macrophages in atherosclerosis and, in humans, the expression of Hdac3 is linked to plaque vulnerability to rupture. <boxed-text content-type="graphic" id="emmm201404170-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text>